2008
DOI: 10.1039/b805540h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-regulated phase behavior of ordered block copolymers

Abstract: Although block copolymer motifs have received considerable attention as supramolecular templates for inorganic nanoparticles, experimental observations of a nanostructured diblock copolymer containing inorganic nanoparticles-supported by theoretical trends predicted from a hybrid self-consistent field/density functional theory-confirm that nanoparticle size and selectivity can likewise stabilize the copolymer nanostructure by increasing its order-disorder transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Recent observations by Gaines et al 46 indicated a tendency for the T ODT to shift slightly upward with the addition of highly selective NPs toward one of the blocks, in agreement with an extension of Timmerman's simple rule to BCP. Tirumula et al 47 recently showed that the addition of a homopolymer with a selective interaction for one of the blocks has the same effect.…”
Section: Discussionsupporting
confidence: 67%
“…Recent observations by Gaines et al 46 indicated a tendency for the T ODT to shift slightly upward with the addition of highly selective NPs toward one of the blocks, in agreement with an extension of Timmerman's simple rule to BCP. Tirumula et al 47 recently showed that the addition of a homopolymer with a selective interaction for one of the blocks has the same effect.…”
Section: Discussionsupporting
confidence: 67%
“…A significant change in either radius of curvature or degree of block segregation, or both, can lead to an order-to-order or an order-to-disorder phase transition [44]. Several studies have shown that NP incorporation into a specific location of ordered BCPs caused order-to-order phase transitions [67,78,118,119,120,121]. In addition to inducing structural transitions, NP incorporation can also influence the characteristic size of the nanodomains [75,122].…”
Section: Page 13 Of 96mentioning
confidence: 98%
“…153 In other applications, the particles are used to modify the self-assembly of the parent block copolymer to lead to new morphologies of self-assembly. 154,155 The resulting structures have been proposed for use in applications such as separation processes, next-generation catalysts and photonic band gap materials.…”
Section: Self-assembly Of Nanoparticles In Block Copolymer Matricesmentioning
confidence: 99%